The Presence of Vacuolated Kupffer Cells Raises a Clinical Suspicion of Niemann-Pick Disease Type C in Neonatal Cholestasis - Wang, Neng-Li; Chen, Lian; Lu, Yi; Xie, Xin-Bao; Lin, Jing; Abuduxikuer, Kuerbanjiang; Wang, Jian-She (Frontiers in Genetics, 2022)
Early diagnosis of Niemann-Pick disease type C (NP-C) in neonatal cholestasis is still challenging because splenomegaly is non-specific and oxysterol profiling studies also have a relatively low specificity. This study explores a method for identifying infants with a high clinical suspicion of NP-C in neonatal cholestasis. We reviewed the clinical findings of 9 neonatal cholestatic infants with NP-C genetically diagnosed between January 2015 and December 2020. Seven underwent liver biopsy at ages ranging from 35 to 112 d. Foam cells were only detected in 2 (28.6%, 2/7) liver tissues obtained beyond 3 months of age. However, vacuolated Kupffer cells were detected in all 7 liver tissues. Their significance was explored by using 168 neonatal cholestatic infants, who underwent genetic tests and liver biopsy between January 2018 and December 2020. Of them, 26 detected vacuolated Kupffer cells. Six (23.1%, 6/26) were diagnosed as NP-C, comparing to none of the 142 neonatal cholestatic infants without vacuolated Kupffer cells (χ2 = 33.983, p < 0.001). The ratio of positive diagnosis of NP-C was 31.6% (6/19) in neonatal cholestatic infants with both vacuolated Kupffer cells and splenomegaly. Therefore, we conclude that the presence of vacuolated Kupffer cells can raise a high clinical suspicion of NP-C in neonatal cholestatic infants, especially in those with splenomegaly.